Sistema de gerenciamento de professores orientadores para os cursos de graduação da Fatec Franca - CARRIJO, Leonardo; MOTA, Pedro Henrique (109, 2025)
This work presents the development of a web-based management system for academic advisors and students enrolled in the Graduation Project course of the Industrial Production Management degree at Faculdade de Tecnologia de Franca – FATEC Dr. Thomaz Novelino. The proposal arose from the need to organize and centralize processes that are currently carried out manually and in a decentralized manner using tools such as email and Microsoft Teams, which hinder monitoring and communication among those involved. The main objective is to provide the course coordinator with an intuitive platform to manage the allocation of students to advisors and the submission of assignments. The methodology involved requirements gathering through forms and interviews, SWOT analysis, application of the 5W2H tool, and modeling using BPMN, use cases, and UML diagrams. As a result, the system offers features such as user registration, task submission, and advisor assignment. It is concluded that the system may improve management by reducing human errors, such as communication failures, and by centralizing information, thus contributing to a more optimized course management process.
Sistema de gerenciamento de professores orientadores para os cursos de graduação da Fatec Franca
Keywords: Automação industrial; Gerenciamento eletrônico de documentos; Informação e Comunicação